Huge (9 Kg) broad ligament fibroid mimicking sarcoma of uterus: A case report and review of literature - Rajshree Dayanand Katke (Wolters Kluwer Medknow Publications, 2017)
Fibroids are most common benign tumors of the uterus, mostly situated in the body of the uterus. Rarely, they arise from extrauterine sites with broad ligament fibroids being uncommon. We present a case of a 47-year-old female, multipara who presented in outpatient department in CAMA hospital with a history of sudden development of dysuria 10 days back. Intraoperatively, uterus was pushed to side and large broad ligament fibroid of 25 cm × 20 cm × 20 cm seen arising from right-sided broad ligament. The fibroid was densely adherent to bowel and bladder. Exploratory laparotomy with excision of broad ligament fibroid of 9 Kg with total abdominal hysterectomy with right salpingo-oophorectomy was done.